2020
DOI: 10.1111/jam.14747
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol promotes mammary cell proliferation and antioxidation capacity during pregnancy and lactation in mice

Abstract: Aims Reproduction can induce maternal oxidative stress, and resveratrol is able to alleviate oxidative stress. This study aimed to investigate the protective effects of resveratrol supplementation in mice during pregnancy and lactation. Methods and Results Pregnant mice were randomly divided into three groups: (i) Pure water (Con); (ii) Cellulose sodium dissolves with 20 mg kg−1 resveratrol (R1) and (iii) Cellulose sodium dissolves with 40 mg kg−1 resveratrol (R2). The experiment starts at pregnancy and ends a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Huang et al [ 75 ] showed that RSV supplementation could not alleviate the reduction in the abundance of Lactobacillus in offspring caused by prenatal and postnatal HFDs. Zha et al (2020) revealed that the offspring of normal mice treated with 40 mg/kg/day of RSV during pregnancy displayed a decreasing trend in the abundance of Lactobacillus in their intestinal tracts [ 76 ]. The results of these previous studies were consistent with those of this study ( Figure 3 B,C), i.e., the results of the operational taxonomic units (OTUs) showed that RBE intake can increase the abundance of S24-7 and decrease the abundance of Lactobacillus.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al [ 75 ] showed that RSV supplementation could not alleviate the reduction in the abundance of Lactobacillus in offspring caused by prenatal and postnatal HFDs. Zha et al (2020) revealed that the offspring of normal mice treated with 40 mg/kg/day of RSV during pregnancy displayed a decreasing trend in the abundance of Lactobacillus in their intestinal tracts [ 76 ]. The results of these previous studies were consistent with those of this study ( Figure 3 B,C), i.e., the results of the operational taxonomic units (OTUs) showed that RBE intake can increase the abundance of S24-7 and decrease the abundance of Lactobacillus.…”
Section: Discussionmentioning
confidence: 99%
“…[ 124 ] Zha and colleagues fed mice resveratrol through pregnancy and lactation and observed increased luminal cell density and increased expression of detoxifying enzymes (UDP glucuronosyltransferase 1, UGT1A1 ; cytochrome P450, CYP1A1 ). Additionally expression of mitophagy genes, such as transcription factor Eβ (Tfeβ), Bcl1lc3β, (Map1lc3β), Parkin, sequestosome1 (p62), autophagy‐related protein ( ATG5 ), and Beclin‐1 ( BECN1 ) are increased in the mammary gland in response to resveratrol, [ 125 ] all of which are important for MEC differentiation into lactocytes. [ 126 ] Resveratrol also prevents H 2 O 2 ‐induced endoplasmic reticulum stress and mitochondria‐related cell apoptosis in MAC‐T cells through decreased expression of GRP8, CHOP, BAX , and BCL2 in a nuclear factor erythroid 2‐related factor 2 (Nrf2)‐dependent manner, through the prolonged activation of insulin signaling pathways such as PI3K/Akt and ERK/MAPK.…”
Section: Resultsmentioning
confidence: 99%
“…Mitophagy is defined as the selective removal of dysfunctional mitochondria by autophagy, a process aberrantly affected by ROS increase and physiologically restored by oxidative stress balance [69]. Consonantly, a study by Zha et al [70] demonstrated that resveratrol supplementation in pregnant mice might promote mammary gland proliferation and antioxidant activity through mitophagy activation [70]. Pregnancy-related metabolic disorders, such as GDM, occur when ROS prevents insulin from facilitating cellular glucose uptake, subsequently leading to insulin resistance [71].…”
Section: Resveratrol's Mechanism Of Action During Pregnancy Complicat...mentioning
confidence: 99%